Mental health problems in children and young people in Dutch general practice: trends in incidence and consultation rates from 2016 to 2022 - Hart, Vincent R. ‘t; Koet, Lukas B. M.; Schouten, Boris W. V.; Velek, Premysl; Bindels, Patrick J. E.; Gerger, Heike (Social Psychiatry and Psychiatric Epidemiology, 2025)
In recent decades, the prevalence of mental health problems among children and young people (CYP) has increased. It is unclear whether this increase in prevalence has also led to changes in health care utilization for these problems in general practice (GP). We therefore investigated time trends in incidence and consultation rates for eight mental health problems in CYP in Dutch general practice. We conducted a longitudinal population-based study using a GP-database (Rijnmond Primary Care Database) between 2016 and 2022. We extracted monthly data on mental health problems in CYP (0-24 years) in general practice. Using negative binomial models, we calculated trends for GP-registered incidence and consultation rates for different age and sex categories for the complete study period and for the period before the COVID-19 pandemic. Consultation rates of all eight mental health problems increased significantly over time. Additionally, incidence rates for attention deficit hyperactivity disorder and depressive problems in both sexes, and anxiety problems in females increased significantly. Although we observed a decrease in incidence and consultations in the first months of the COVID-19 pandemic, overall trends did not differ from pre-pandemic trends. Our findings suggest an increasing workload for GPs for mental health problems in CYP. These observations imply the need for policymakers and GP-councils to develop new strategies which deal with these trends to ensure appropriate support and resources in the future.